‘I feel like I am more respected here in Thailand’: Indonesian EFL Teachers' Experiences and Challenges in Thai Elementary Schools (Universitas Muhammadiyah Yogyakarta, 2023)
With the growth of teacher mobility, where teachers from diverse cultural backgrounds attempt to broaden their teaching experiences, the resulting global community has given rise to new and challenging educational environments. In Thailand, numerous English programs welcome teachers from different countries, accordingly contributing to the nuances of foreign English teachers' experiences. This study aims to delve into the experiences and challenges faced by Indonesian EFL teachers working in Thailand. In the context of the globalized educational system, the inclusion of Indonesian teachers in this study is essential. Their distinct cultural experiences and challenges not only enhance multicultural understanding but also contribute significantly to the existing literature on teaching English in foreign settings. Utilizing a qualitative research approach, this study conducted multiple semi-structured interviews with two Indonesian EFL teachers employed in both a public elementary school and a private elementary school in Thailand. The findings reveal that teaching English in Thailand has provided them with valuable insights and has been a transformative experience, enhanced their professional growth. The findings also provide comprehensive insights into the unique challenges faced by these teachers, particularly regarding language barriers, cultural adaptation, and professional relationships. This study not only illuminates the challenges encountered by teachers but also underscores the considerable potential for personal and professional growth within the ever-evolving landscape of teaching English oversea.